Histopathological analysis of Cholecystectomy specimens - De zoysa, M.I.M.; De Silva, S.K.L.A.; Illeperuma, A.; Liyanarachchi, N.K. (My University, 2012)
Laparoscopic or open cholecystectomy is the treatment for symptomatic gallstones. It is a routine practice in our hospital to send the gallbladders removed for histopathological analysis regardless of visible or palpable macroscopic abnormality. The main aim of histological assessment is to detect primary gallbladder carcinoma which is rare. This increases the workload of the histopatologists and the cost of processing specimens.